Clinicopathological features and outcome of type 3 gastric neuroendocrine tumours. Issue 11 (12th June 2018) - Min, B-H; Hong, M; Lee, J H; Rhee, P-L; Sohn, T S; Kim, S; Kim, K-M; Kim, J J
Abstract: Background: With the widespread use of endoscopy, small and low-grade type 3 gastric neuroendocrine tumours (NETs) are increasingly being detected. The clinicopathological features, biological behaviour and appropriate treatment strategy for these NETs remain unclear. Methods: Patients with biopsy-proven gastric NET and a normal fasting serum gastrin level were identified from a prospectively maintained database. Clinicopathological features and long-term outcome of local resection for type 3 NETs were reviewed retrospectively and compared according to tumour grade. Results: Some 32 patients with type 3 gastric NETs were included (25 patients with NET grade G1, 5 with G2 and 2 with G3). Pathological tumour size was 2·0 cm or less in 30 patients. All tumours were well differentiated, even G3 lesions, and all tumours but one were confined to the submucosal layer. G1 NETs were significantly smaller and had a significantly lower lymphovascular invasion rate than G2 and G3 NETs. Twenty-two patients with a G1 NET without lymphovascular invasion were treated with wedge or endoscopic resection. After a median follow-up of 59 (range 6–102) months, no patient with a G1 NET of 1·5 cm or smaller developed recurrence and one patient with a G1 NET larger than 1·5 cm had recurrence in a perigastric lymph node. Among seven patients with a G2 or G3 NET, two had lymph node metastasis and one had liver metastases. Conclusion: Low-grade type 3 gastric NET has non-aggressive features and a favourable prognosis. Wedge or endoscopic resection may be a valid option for patients with type 3 gastric G1 NET no larger than 1·5 cm without lymphovascular invasion. Abstract : Limited resection suffices in selected patients